Development of a PCR Method to Detect a Mysid Species Causing False Positives in Tests for Crustacean Allergens - Hosokawa, Aoi; Sugano, Yohei; Aotuka, Keiji; Suzuki, Tomohiro (Food Hygiene and Safety Science (Shokuhin Eiseigaku Zasshi), 2024)
Mysids are small crustaceans that are closely related to shrimp/prawns and crabs but not subject to food allergen labeling requirements for raw materials. In the past, a processed food that contained Japanese smelt (wakasagi) was suspected of producing a false-positive result in shrimp/prawn and crab allergen test because of the presence of consumed mysids. However, there was no reported methods to confirm mysid presence. Therefore, we developed a PCR method to detect mysids. The developed PCR method had high specificity for a mysid species, with no amplification observed from samples of shrimp, crab, krill, mantis shrimp, or the meat of Japanese smelt. In addition, DNA extracted from the internal organs of Japanese smelt was amplified by this PCR method, and sequencing revealed mysid DNA. This confirmed that mysids remained in the internal organs of Japanese smelt following consumption. This PCR method for mysid detection even amplified Japanese smelt-containing processed food samples that were suspected to have produced a false-positive result in shrimp/prawn and crab ELISA. Thus, this PCR method would enable to detect such false positives are caused by mysid contamination.